Stakeholders' experience of the innovative ways of coproducing neighborhood security in Johannesburg, South Africa - Mlamla, Likhona Mihlali; Mangai, Mary S.; Masiya, Tyanai; Holtzhausen, Natasja (Technium Social Sciences Journal, 2022)
Johannesburg is known to be the crime capital in South Africa. This hinders investment opportunities for the country and causes insecurities for citizens. This article analyzed the current neighborhood security challenges and sought to develop an innovative and inclusive model of co-producing neighborhood security in the City of Johannesburg based on the unstructured interviews with police officers in Johannesburg which were analyzed using a qualitative approach. The study found that the challenges of neighborhood security in Johannesburg include socio-economic status, crime, lack of trust, and inadequate resources. Moreover, inclusivity promoted community involvement and effective participation from the South African Police Service, civil society, and government whilst innovation utilized technological methods such as social media, radio shows, and newspapers which ensured that the insecurities were eliminated and that the crime rate in Johannesburg decreasesI